The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1080/1024529042000301935
|View full text |Cite
|
Sign up to set email alerts
|

Creating Lean Industrial Relations: General Motors in Silao, Mexico

Abstract: Research demonstrates that firms tailor their 'lean production' systems to take advantage of local cultural, industrial and labour relations environments to enhance productivity and at specific worksites. This article analyses the human resource policies practised by General Motors (GM) and their suppliers in Silao, Mexico to identify two local innovations to the automaker's lean production system. First, GM achieved the labour stability necessary to implement lean production by meticulously selecting workers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A philosophy that shortens the time between customer order and shipment of the final product 10 Storch and Lim (1999) An efficient way to satisfy customers and increase competitiveness 11 Howell (1999) A new way to optimize performance of the production system 12 Comm and Mathaisel (2000) A philosophy that significantly reduces cost and cycle time throughout the entire value chain 13 Liker and Wu (2000) A philosophy toward delivering highest quality product on time and at the lowest cost 13 Shah and Ward (2003) An approach to deliver the upmost value to the customer 14 Alukal (2003) A philosophy that shortens lead time between customer order and shipment of the products 15 Hopp and Spearman (2004) An integrated system that accomplishes production of goods/services with minimal buffering costs 16 Haque and Moore (2004) Eliminating waste and improving the flow of value 17 Rothstein (2004) An array of manufacturing system that include many tools 18 Worley (2004) Systematic removal of waste by all staff from all areas of a firm 19 Simpson and Power (2005) An efficient and well-organized generating system for continuous improvement and waste elimination 20 Seth and Gupta (2005) Continuous minimizing of waste to maximize flow 21 Taj and Berro (2006) Manufacturing without waste 22 Shah and Ward (2007) Lean is a management philosophy focused on identifying and eliminating waste throughout a product's entire value stream, both within the organization and along its entire supply chain network (the best definition selected by the author of this paper) 23 Holweg (2007) Extends the scope of Toyota Production philosophy to product development process, supplier management process, customer management process and policy-focusing process 24 Taj and Morosan (2011) A multidimensional approach that consists of JIT, Cellular Layout, TPM, TQM and HRM that has positive impact on operations/competitive performance 25 Zahraee et al (2014b) An efficient technique to sustain competitiveness in an expanding global market Lean manufacturing to eliminate waste by concurrently reducing or minimizing supplier, customer and internal variability".…”
Section: Sn Scholarsmentioning
confidence: 99%
“…A philosophy that shortens the time between customer order and shipment of the final product 10 Storch and Lim (1999) An efficient way to satisfy customers and increase competitiveness 11 Howell (1999) A new way to optimize performance of the production system 12 Comm and Mathaisel (2000) A philosophy that significantly reduces cost and cycle time throughout the entire value chain 13 Liker and Wu (2000) A philosophy toward delivering highest quality product on time and at the lowest cost 13 Shah and Ward (2003) An approach to deliver the upmost value to the customer 14 Alukal (2003) A philosophy that shortens lead time between customer order and shipment of the products 15 Hopp and Spearman (2004) An integrated system that accomplishes production of goods/services with minimal buffering costs 16 Haque and Moore (2004) Eliminating waste and improving the flow of value 17 Rothstein (2004) An array of manufacturing system that include many tools 18 Worley (2004) Systematic removal of waste by all staff from all areas of a firm 19 Simpson and Power (2005) An efficient and well-organized generating system for continuous improvement and waste elimination 20 Seth and Gupta (2005) Continuous minimizing of waste to maximize flow 21 Taj and Berro (2006) Manufacturing without waste 22 Shah and Ward (2007) Lean is a management philosophy focused on identifying and eliminating waste throughout a product's entire value stream, both within the organization and along its entire supply chain network (the best definition selected by the author of this paper) 23 Holweg (2007) Extends the scope of Toyota Production philosophy to product development process, supplier management process, customer management process and policy-focusing process 24 Taj and Morosan (2011) A multidimensional approach that consists of JIT, Cellular Layout, TPM, TQM and HRM that has positive impact on operations/competitive performance 25 Zahraee et al (2014b) An efficient technique to sustain competitiveness in an expanding global market Lean manufacturing to eliminate waste by concurrently reducing or minimizing supplier, customer and internal variability".…”
Section: Sn Scholarsmentioning
confidence: 99%
“…Haque and Moore (2004) Lean is by definition an enterprise initiative with a common format for all business processes with the single strategic goal of eliminating waste and improving the flow of value 22. Rothstein (2004) Lean production is more commonly considered as a broad production paradigm including an array of manufacturing systems containing some variety of lean practices, such as justin-time inventory systems, teamwork, multi-tasking, employee involvement schemes, and policies for ensuring product quality throughout the production process (continued )…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Latin America, existing research has shown how national culture can affect management processes in small and medium businesses as well as in multinational corporations (e.g. see Rothstien, 2004;Athanassiou et al, 2002 for the case of Mexico). Despite this important fact, until now there is little empirical evidence of the existence of clear patterns showing how national culture of a given country affects management processes in systematic ways.…”
Section: Discussionmentioning
confidence: 99%